Spanish - ZAMARRIPA MARTÍNEZ, Eduardo (Journal of the Spanish Institute for Strategic Studies, 2023)
There is no doubt that nuclear weapons condition international relations, they have done so throughout the Cold War and will continue to do so in the future. The efforts of the international community, mainly within the framework of the United Nations, to regularize and even eliminate this type of weapons have helped to maintain the current international system but have not been able to eradicate them. The most provocative question is whether its elimination would favor peace between states or provoke a greater number of conventional conflicts, even among the world’s greatest powers, which are currently far from friendly relations.